The Application of CRISPR/Cas Technology to Efficiently Model Complex Cancer Genomes in Stem Cells. Issue 1 (11th July 2017) - Albitar, Adam; Rohani, Bahar; Will, Brett; Yan, Annie; Gallicano, G. Ian
ABSTRACT: CRISPR/Cas gene editing technologies have emerged as powerful tools in the study of oncogenic transformation. The system's specificity, versatility, and ease of implementation allow researchers to identify important molecular markers and pathways which grant cancers stem cell like properties. This technology has already been applied to researching specific cancers, but has seen restricted therapeutic applications due to inherent ethical and technical limitations. Active development and adaptation of the CRISPR/Cas system has produced new methods to take advantage of both non‐homologous end joining and homologous recombination repair mechanisms in attempts to remedy these limitations and improve the versatility of gene edits that can be created. Nonetheless, until issues with specificity and in vivo efficiency are resolved, utilization of CRISPR/Cas systems would be best employed in the modeling and study of various cancer genes. While it may have potential therapeutic applications to targeted cancer therapies in the future, presently CRISPR/Cas is a remarkable technique that can be utilized for easy and efficient gene editing when it comes to cancer research. J. Cell. Biochem. 119: 134–140, 2018. © 2017 Wiley Periodicals, Inc. Abstract : CRISPR/CAS9 technology is being used manipulate genomes of many different types of organisms. While it may be used in the future to correct genetic mutations in vivo, one current powerful use for CRISPR technology is to edit genes for modeling various types of cancers for use in cancer research.